On the Quantum Mechanics of Entropic Forces - Daniel Carney; Manthos Karydas; Thilo Scharnhorst; Roshni Singh; Jacob M. Taylor (Physical Review X)
It was conjectured 30 years ago that gravity could arise from the entropic rearrangement of information. We offer a set of microscopic quantum models which realize this idea in detail. In particular, we suggest a simple mechanism by which Newton’s law of gravity arises from extremization of the free energy of a collection of qubits or oscillators, rather than from the exchange of virtual quanta of a fundamental field. We give both a local and a nonlocal version of the construction and show how to distinguish a range of these entropic models from ordinary perturbative quantum gravity using existing observations and near-term experiments.